Biochemical composition, oil profiling and elemental analysis of different cumin (Cuminum cyminum L) genotypes: Biochemical and elemental analysis of cumin genotypes - Gamit, N S; Litoriya, N S; Thounaojam, A S; Patel, P K (Journal of Spices and Aromatic Crops, 2023)
Cumin (Cuminum cyminum L.) is an annual plant of the family Apiaceae and the genus Cuminum has a single species Cyminum, native from the east Mediterranean to east India. In India, Gujarat and Rajasthan are the major producing states. After black pepper, cumin is the second most popular spice in the world. The present research work was carried out to study the nutritional quality parameters, oil profiling and element composition of fifteen cumin genotypes. The results showed that the moisture content was found to vary from 6.22 to 8.15 %. The carbohydrate content was higher in Kushalpura-1 (46.14 %), while the crude protein was highest in Indawar followed by GC-2 and Merta-2. Total protein content was highest in Lampolai (18.24 %) and lowest in GC-2 (11.36 %). In Lamba Jatan, highest content of non-reducing sugars (8.35 %) and total soluble sugars (9.11 %) were observed. Reducing sugars was detected in the range of 0.72 – 1.53 %. Highest amount of total free amino acids and crude fiber were found in Gawardi and Kushalpura-1, respectively. The total oil (20.27 %) and volatile oil (3.99 %) content were highest in GC-4. The petroselinic acid and linoleic acid were observed as primary fatty acids in all tested genotypes. However, Lampolai, Merta-1, GC-2 and GC-4 were good sources of both fatty acids among all the genotypes. The elemental analysis showed that the GC-2 has a high overall amount of macronutrients, while micronutrients was highest in Piplon-5.